Isovaleric acidemia: clinical presentation of 6 cases - Tokatlı, Ayşegül; Coşkun, Turgay; Özalp, İmran (The Turkish Journal of Pediatrics, 1998)
A retrospective study is reported on the clinical outcome of six patients with Isovaleric acidemia (IVA) diagnosed during the last 20 years at the Metabolic Unit of Hacettepe University Children’s Hospital. IVA is only one of many inborn errors of metabolism that may have an acute or a late, intermittent presentation. Generally, the diagnosis cannot be made by clinical or routine clinical chemical investigations, although the odor of “sweaty feet” is a presenting symptom. An unusual urinary odor, which was present in all of our patients, should lead to a thorough screening for organic acidemia at any age. Here, we have reported six patients with IVA. Two pairs were siblings. All, except one patient, had positive family history of sibling deaths and all parents were related. In our series, only two patients presented during the neonatal period and both died during the acute crisis. The other four patients presented after the neonatal period and were categorized as having a chronic intermittent form of IVA. Two cases showed normal development despite repeated metabolic decompensations; one patient was diagnosed during the first attack, but he was mentally and motor retarded. The other one died during the metabolic crisis. The presented cases clearly illustrate that IVA can be managed successfully once the diagnosis is made. But lack of early recognition may lead to severe psychomotor retardation or death.